Toxicity studies of some medicinal plant extracts - Sukari, Mohd Aspollah; Rahmani, Mawardi; Desa, Mohd Zaizi; Manas, Abd Rahman; Yusof, Omar; Ahmad, Md shukur; Takahashi, Shozo (Dept. of Chemistry, Institut Teknologi Bandung, 1989)
Toxicity studies of some labiate, Zingiberaceae and Euphorbiaceae plants including Ocimum sanctum, Mentha arvensis, Curcuma viridiflora, C. zedoaria, Antidesma tomentosum and Isotoma longiflora were investigated. The volatile fraction of some of these medicinal plants were isolated and the chemical components of the extracts were characterized by gas chromatography and spectroscopic methods. This report discusses the contact insecticidal activity test of the plant extracts against red bean weevil (Callosobrunchus chinensis) and mung bean weevil (C.maculotus), and the inhibition of the seed germination test of rice seeds (Oryza sativa) and mung bean (Phaseolus aureus). The result on the toxicity test certain plant extracts on two species of fish, Tilapia mossambica and Lesbistes reticulatus and the determination of LC50 values will also be presented.